Zitelli and Davis' Atlas of Pediatric Physical Diagnosis - Zitelli, B. J. Basil J. (Elsevier, 2018)
The most trusted, most consulted resource for rapid identification and diagnosis of hudreds of pediatric disorders. Through six bestselling editions, Zitelli and Davis' Atlas of Pediatric Physical Diagnosis, by Drs. Basil J. Zitelli, Sara C. McIntire, and Andrew J. Nowalk, has been the gold standard atlas of pediatric diagnosis for residents and physicians. Thousands of high-quality clinical photographs are paired with authoritative clinical content, covering both common and uncommon pediatric disorders. Extensive revisions throughout bring this encyclopedic resource fully up to date, helping you hone your visual examination skills and improve your diagnostic accuracy. Features more than 2,500 color photographs supplemented by explanatory text, laboratory tests, and imaging. Emphasizes pertinent historical factors, examination techniques, visual findings, and diagnostic methods. Includes over 20 clinical videos online, as well as new coverage of urinary tract infections, vesicoureteral reflux management, food allergies, Lyme disease, coagulation disorders, congenital infections, and immune deficiencies. Contains a new chapter on vascular anomalies, with detailed descriptions of vascular malformations and new medical co-management approaches. Expert Consult™ eBook version included with purchase. This enhanced eBook experience allows you to search all of the text, figures, and references from the book on a variety of devices.